PLD and PI3K signaling in neuronal oxidative stress - Salvador, Gabriela Alejandra (2015)
Lipid signaling cascades have important roles in the regulation of cellular fate. Our studies provide new insights into the regulation and physiological role of lipid messengers during neuronal oxidative stress (OS). Specifically, we have studied neuronal signal events derived from phosphatidylcholine (PC) and phosphatidylinositol (PI). Synaptic OS triggers phospholipase D (PLD) activation and, consequently, a rise in phosphatidic acid and diacylglycerol (DAG) generation from PC. These lipid messengers activate downstream signaling cascades as ERK1/2 and conventional PKCs and regulate glutamate transport in the synaptic cleft of adult rat brains. Studies in aged brains reveal an increased synaptic susceptibility to OS and an impairment in the DAG-mediated signaling pathways. Tyrosine phosphorylation associated with PI phosphorylation and phosphoinositide 3 kinase (PI3K) activation are stimulated in OS-exposed hippocampal neurons and synapses. PI3K activation and its downstream effector kinase, Akt, trigger pleiotropic neuroprotective mechanisms against OS by suppressing FOXO3A transcriptional activity, inhibiting GSK3β and upregulating glutathione metabolism. In summary, we have characterized signaling events elicited by PLD and PI3K activation, which produce lipid messengers that control smart strategies for preventing neuronal death triggered by OS.